Potential Agricultural Practices in Saline Waterlogged Areas of Haryana and their Impact on Socio-economic Conditions of Farmers – A Synthesis: Socio-economic impact of potential agricultural practices on farmers - SS Grewal; HS Lohan; JC Dagar (Journal of Soil Salinity and Water Quality, 2023)
Paradoxically, in India 147 million hectares (m ha) land is reported to be suffering from different processes of land degradation and about 14.3 and 8.6 m ha area suffers from waterlogging and permanent submergence, respectively. In the fast-developing state of Haryana having acute scarcity of cultivated lands, 0.45 m ha (around 10 percent of total geographical area) suffers from the problem of waterlogging and salinity. Such problem imposes, serious limitations for raising crops at least in eight south-western districts namely Rohtak, Jhajjar, Charkhi Dadri, Bhiwani, Hisar, Jind, Sirsa and Fatiabad, and adversely affects the cropping pattern and crop productivity resulting in huge socio-economic losses. The problem of waterlogging got aggravated in late sixties and early seventies when the irrigated areas of these districts were brought under paddy cultivation which required excessive irrigation. To tackle these problems, some sub-surface drainage projects were undertaken by the institutes like Central Soil Salinity Research Institute, Karnal and Haryana Agriculture University Hisar in the form of Indo-Dutch collaborative projects. In addition to those many other research efforts were made by these institutes and several agricultural practices were developed. The present studies were undertaken to review the nature of problems being faced by the farmers, possible solutions based upon lessons-learnt from research and implementation experiences and also dovetailing the perceptions of the farmers as key players. Such an exercise may help to identify best agricultural practices, their need and scope of management of saline and waterlogged areas. The primary objectives of this study were comprehensive review of waterlogging and salinity problems in the state; critical analysis of the projects implemented showing the impacts on hydrology, salinity levels, crop production and productivity; emerging best agricultural practices in terms of socio-economic implications; and farmers’ perceptions about constraints, bottlenecks in implementation of subsurface drainage projects.